New data on a cultural control method against coconut lethal yellowing in Ghana - R. Philippe; S. K. Dery; J. Nkansa Poku (International Coconut Community, 2004)
Lethal yellowing disease has been rife in West Africa, especially Ghana, since 1932. In the 1990s, the first operations to fell diseased coconut palms at an early stage showed that this substantially slowed down the spread of the disease. Trial conducted in 1995 showed that early felling of diseased coconut palms, even without prior treatment, considerably slowed down the spread of the disease. Replications of this action in several other plots kept them healthy for many years. These positive results made it possible to obtain funding from Agence française de Développement (AFD) to maintain a